Synthesis of 9-O-arylated berberines via copper-catalyzed CAr–O coupling reactions - Teng, Qiaoqiao; Zhu, Xinhui; Guo, Qianqian; Jiang, Weihua; Liu, Jiang; Meng, Qi (Beilstein Journal of Organic Chemistry, 2019)
Berberine is a widely used antimicrobial agent in clinic. However, a high dosage is often required due to its low lipophilicity and bioavailability. The current study explores the structural modifications of berberines with potentially lipophilic aryl groups to address this problem. A series of 15 9-O-aryl-substituted berberines (3a–o) and one 9-O-phenylene-bridged berberine dimer (5) was synthesized by copper-catalyzed cross-coupling of tetrahydroberberrubine and aryl iodides, followed by oxidation with I2.
Keywords: arylation; berberines; cross-coupling; copper; lipophilicity; structural modification